Organizadores visuales en el rendimiento académico de los estudiantes del tercer grado de secundaria del centro educativo César Vallejo en el año 2024 - Cuya García, Isaías (2025)
The objective of this research was to determine the use of visual organizers before and after the academic performance of third grade high school students at the César Vallejo Educational Center in 2024. The research was correlational and applicative. The population made up of 3rd grade high school students at the César Vallejo Educational Center in 2024, making a total of 108 students, the sample was selected non-randomly by convenience by selecting 25 students (Women), where the male sex was excluded, leaving only the female sex. As a result, tc = 5.778, tt = 3.355 was obtained, observing that tc> tt accepting the hypothesis: Visual organizers will have a significant statistic before and after the academic performance of third grade high school students at the César Vallejo Educational Center in 2024. And it was concluded that of 100% of students; Before applying the use of visual organizers, 56.52% of the students indicated that their academic performance was LOW, and after applying the use of visual organizers, 63.20% of the students indicated that their academic performance was REGULAR. Therefore, it can be observed that the visual organizers had an effect on academic performance, which is statistically significant when relating the results before and after the application of the visual organizers.